Authorea
DOI: 10.22541/au.158739987.76562417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of pregnant women with COVID-19: a systematic review and meta-analysis

Abstract: Background: COVID-19 outbreak in Wuhan, China recently. It quickly spread throughout. Objectives: To investigate clinical features and outcomes of pregnant women with COVID-19. Search Strategy: PubMed、Web of Science、EMBASE、MEDLINE were searched from January 1, 2020 to April 16, 2020. Selection Criteria: Case review of pregnant women infected with COVID-19 Data Collection and Analysis: Two reviewers screened 366 literatures and 14 studies included, four reviewers independently extracted the features of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 28 publications
2
47
0
4
Order By: Relevance
“…After the application of the eligibility criteria, 39 studies were finally included [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], one (2.6%) of which was described as “rapid” [ 42 ] and two (5.1%) as “scoping” systematic reviews [ 30 , 50 ]. Thirteen (33%) of them also undertook a meta-analysis [ 14 , 16 , 18 , 19 , 24 , 25 , 27 , 36 , 38 , 40 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the application of the eligibility criteria, 39 studies were finally included [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], one (2.6%) of which was described as “rapid” [ 42 ] and two (5.1%) as “scoping” systematic reviews [ 30 , 50 ]. Thirteen (33%) of them also undertook a meta-analysis [ 14 , 16 , 18 , 19 , 24 , 25 , 27 , 36 , 38 , 40 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen (33%) of them also undertook a meta-analysis [ 14 , 16 , 18 , 19 , 24 , 25 , 27 , 36 , 38 , 40 , 48 , 49 , 52 ]. Twenty-nine (74%) reviews evaluated quality of individual studies [ 14 , 15 , 16 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 37 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 51 , 52 ], with one of them doing so, in a subjective manner, without utilizing any assessment tool [ 42 ]. Among the eligible systematic reviews’ last search dates, the most recent one took place on 8 July 2020.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to changes in the immune system in pregnant women. Currently, there is no evidence that pregnancy alleviates symptoms of the disease and more studies are needed to confirm this [13]. This result is similar to a new meta-analysis published in early September 2020: Pregnant women infected with SARS-CoV-2 have less symptoms of fever (OR 0.43, 95% CI 0.22-0.85) and myalgia (OR 0.48, 95% CI 0.45-0.51) compared with non-pregnant women infected with SARS-CoV-2 [6].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, as of early September 2020, there have been 07 meta-analyzes and systematic reviews of pregnancy outcomes in SARS-CoV-2 infected pregnant women published in English. Results of 06 meta-analyzes and systematic reviews all showed that the rate of preterm birth and cesarean section in pregnant women infected with SARS-CoV-2 was higher than in women without SARS-CoV-2 [6,7,13,14,18,19], meanwhile, 01 meta-analysis by Melo, et al had the opposite result, that COVID-19 infection in pregnant women might not associated with preterm birth [9]. However, the authors of these meta-analyzes and systematic reviews all argue that cautions should be taken when interpreting the results due to limitations (i.e most of studies were retrospective studies and case reports; and lack of high quality evidence).…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Sehingga apabila ada gangguan kesehatan pada ibu hamil, ia akan langsung dibawa ke fasilitas kesehatan untuk segera diperiksa sehingga dan hal ini berimplikasi pada penurunan keterlambatan dalam tatalaksana. Penanganan awal ini juga menurunkan risiko gejala klinis ibu hamil untuk berkembang menjadi berat (Gao et al, 2020;Zeng et al, 2020;Qiancheng et al, 2020) Selanjutnya penelitian yang dilakukan oleh Zeng et al mengungkapkan suatu fakta, nyaitu apabila dilakukan perbandingan antibodi IgG SARS-CoV-2 antara pria dan wanita, maka wanita dengan infeksi COVID-19 akan memiliki antibodi yang jauh lebih tinggi. Produksi antibodi ini sangat tinggi pada awal infeksi, dan ini yang menjelaskan mengapa wanita termasuk ibu hamil memiliki gejala klinis yang relatif lebih ringan dibandingkan dengan pria.…”
Section: Hasil Dan Pembahasanunclassified